A method for preparing artificial graphite secondary particles

By mixing raw material coke with liquid phase additives and pressing them into blocks, pre-carbonizing and graphitizing, and finally crushing the finished particles, the problems of high energy consumption and poor operating environment in the existing technology are solved, and energy consumption reduction and operating environment are achieved. improve.

CN116119655BActive Publication Date: 2024-12-17河南中炭新材料科技有限公司 +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202211696915.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-28
Publication Date
2024-12-17
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

The existing artificial graphite secondary particle manufacturing process has problems of high energy consumption, high cost and poor operating environment, especially in the process of pre-carbonization and graphitization, which affects workers' health.

Method used

A new preparation method is adopted, including mixing raw material coke with liquid phase additives and pressing into blocks, leaving the through holes for drying, pre-carbonizing and graphitizing, and finally crushing the finished granules, reducing the use of heat treatment equipment and increasing the normal temperature. The crushing process reduces energy consumption and improves the working environment.

Benefits of technology

It significantly reduces production energy consumption and costs, reduces dust emissions, improves workers' working environment, and improves production efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116119655B_ABST
    Figure CN116119655B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing artificial graphite secondary particles, comprising the following steps: S1. Fully mixing raw coke and liquid additives; S2. Pressing and forming into a block product, reserving through holes on the block product, and then drying; S3. Pre-carbonizing the dried block product to obtain a carbonized product; S4. Graphitizing the carbonized product to obtain a graphitized product; S5. Crushing the graphitized product to a finished product index particle size to obtain artificial graphite secondary particles. This application innovates the production process route of artificial graphite secondary particles, reduces the granulation process, and increases the crushing process after graphitization, greatly reducing production energy consumption and production costs; and the dust volume of the pre-carbonization and graphitization processes is greatly reduced, and the working environment of personnel is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of artificial graphite negative electrode materials, and in particular relates to a method for preparing artificial graphite secondary particles. Background Art

[0002] In the field of artificial graphite negative electrode material manufacturing, the production of secondary particles is an important component. The advantages of large particles are high compaction density and high capacity, while small particles have a large specific surface area, more channels for lithium ion migration, shorter paths, and better rate performance. Therefore, the secondary particles that are a composite of large and small particles take into account the advantages of both, which can reduce the expansion of the negative electrode after lithium insertion, improve the liquid retention performance of the negative electrode material, and reduce the orientation degree of the negative electrode material of the pole piece, reducing the impedance caused by polarization.

[0003] At present, the main processing technology of secondary particles is to mix the primary particles of coke that have been crushed to a certain particle size distribution - usually D10 is below 7μm, D90 is below 25μm - with a specific proportion of asphalt and enter the horizontal / vertical reactor for heating. This process is called granulation. During the granulation process, small particles are compounded with small particles, small particles are compounded with large particles, and large particles are compounded with large particles to form secondary particles. Because the particles distributed around D50 occupy the largest volume distribution, this part of the particles has the highest probability of contacting with particles smaller than it and with particles larger than it. Therefore, the morphology after granulation is mostly a composite particle of large particles and small particles. After granulation, the powder material is manually introduced into the tunnel kiln for pre-carbonization and into the graphitization furnace for graphitization by using an overhead crane. Granulation usually heats the material to 550-650℃ and keeps it warm for 4-8h. It is a high-energy consumption and high-cost process. For every 10w tons of annual production, about 120 reactors with a capacity of 1.6t are required to work continuously. Moreover, a large amount of dust is inevitably generated during the loading and unloading process in the pre-carbonization and graphitization process, and the working environment of the on-site personnel is poor.

[0004] In view of the above shortcomings, the present application provides a new secondary particle processing technology, which greatly saves the energy consumption of the reactor and improves the manual working environment during the pre-carbonization and graphitization process. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing artificial graphite secondary particles in order to solve the deficiencies of the prior art.

[0006] The purpose of the present invention is achieved by the following technical solutions:

[0007] A method for preparing artificial graphite secondary particles comprises the following steps:

[0008] S1. The raw coke and the liquid additive are fully mixed;

[0009] S2. Pressing and forming the product into a block, and reserving a through hole on the block, and then drying;

[0010] S3. Pre-carbonizing the dried block product to obtain a carbonized product;

[0011] S4. graphitizing the carbonized product to obtain a graphitized product;

[0012] S5. The graphitized product is crushed to a particle size corresponding to a finished product to obtain secondary artificial graphite particles.

[0013] Preferably, the particle size of the raw coke in step S1 is 2 to 15 μm.

[0014] Preferably, the liquid phase additive in step S1 is one or a combination of two or more selected from coal tar, asphalt oil, liquid asphalt, ethanol mixed liquid of toluene, and ethanol solution of phenolic resin; the amount of the liquid phase additive is 1-15% of the mass of the raw coke.

[0015] Preferably, the molding method in step S2 is hydraulic molding, and the molding pressure is 260-360 Kg / cm 2 , maintain pressure for 2 to 4 minutes.

[0016] Preferably, the maximum diameter or side length of the block is no more than 150 mm, the thickness is no more than 40 mm, the total area of ​​the through holes is no more than 12% of the area of ​​the plane where they are located, and the centers of the through holes are evenly distributed in the side length and diagonal or diameter direction of the block.

[0017] Preferably, the bulk density of the block product is not greater than 0.91 g / cm 3 .

[0018] Preferably, the through holes include a central through hole and a plurality of peripheral through holes evenly distributed around the central through hole, the diameter of the central through hole is 1.5 to 2 times that of the peripheral through holes, and the diameter of the peripheral through holes is 10 to 13% of the side length or diameter of the block product.

[0019] Preferably, the drying temperature in step S2 is 80-150° C. and the drying time is 30-150 min;

[0020] The pre-carbonization temperature in step S3 is 750-900°C and the time is 240-360min;

[0021] The graphitization temperature in step S4 is 2950-3050° C., and the power supply time is 19-20 hours.

[0022] Preferably, in step S4, the carbonized products are loaded into a graphitization furnace charge compartment for graphitization treatment. The carbonized products are loaded into the furnace in pairs and placed in contact with each other, and resistor materials are filled in the gaps between the carbonized products and the walls of the graphitization furnace charge compartment, and resistor materials are also filled in the gaps between adjacent carbonized products.

[0023] Preferably, in step S5, the pulverization is first performed by jaw crusher to millimeter-sized particles, and then further performed by ball mill or impact mill to the target particle size of the finished product, wherein the target particle size of the finished product is 10 to 25 μm.

[0024] The present application innovates the production process of artificial graphite secondary particles, reduces the granulation process, and adds a post-graphitization crushing process. The former is a heat treatment equipment with an energy consumption of 100 to 130 (KW·h) / (day·ton), and the latter is a room temperature treatment equipment with an energy consumption of 25 to 35 (KW·h) / (day·ton), which greatly reduces production energy consumption and production costs; and the amount of dust in the pre-carbonization and graphitization processes is greatly reduced, and the working environment of personnel is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the structure of a square block product;

[0026] Figure 2 It is a schematic diagram of the structure in which multiple square blocks are superimposed;

[0027] Figure 3 It is a schematic diagram of the structure of a cylindrical block product;

[0028] Figure 4 It is a schematic diagram of the structure in which multiple cylindrical blocks are superimposed;

[0029] Figure 5 It is a schematic diagram of the structure of a square block product loading furnace;

[0030] Figure 6 It is a schematic diagram of the structure of a cylindrical block product charging furnace; Figure 7 is a scanning electron microscope image of the artificial graphite secondary particles obtained in Example 1;

[0031] Figure 8 is a scanning electron microscope image of the artificial graphite secondary particles obtained in Comparative Example 1;

[0032] Fig. 9 is a scanning electron microscope image of the artificial graphite secondary particles obtained in Example 2;

[0033] Fig.10 is a scanning electron microscope image of the artificial graphite secondary particles obtained in Example 3;

[0034] Fig.11is a scanning electron microscope image of the artificial graphite secondary particles obtained in Example 4;

[0035] Fig.12 This is a schematic diagram of the structure of the spray furnace in Comparative Example 2;

[0036] Fig.13 This is a schematic diagram of the graphitized product in Example 3 that is broken.

[0037] Among them, 1-material compartment; 2-block product; 3-resistance material. DETAILED DESCRIPTION

[0038] The present invention provides a method for preparing artificial graphite secondary particles, comprising the following steps:

[0039] S1. The raw coke and the liquid additive are fully mixed; the liquid additive mainly acts as a binder, and can be selected from coal tar, asphalt oil (mainly refers to oil extracted from asphalt), liquid asphalt (mainly refers to asphalt products diluted with gasoline, kerosene, diesel and other solvents by petroleum asphalt, also known as light asphalt or diluted asphalt), ethanol mixed liquid of toluene, ethanol solution of phenolic resin, etc., one or more combinations thereof;

[0040] S2. Pressing and forming the product into a block, leaving a through hole in the block, and then drying;

[0041] S3. Pre-carbonizing the dried block product to obtain a carbonized product;

[0042] S4. graphitizing the carbonized product to obtain a graphitized product;

[0043] S5. Grind the graphitized product to a particle size specified by the finished product to obtain secondary artificial graphite particles.

[0044] Compared with the prior art, after the raw coke and the liquid additive are mixed, the present application does not adopt the method of high-temperature granulation and then crushing and screening after granulation, but instead presses it into shape at low temperature, and then directly pre-carbonizes and graphitizes the formed block product. Since the density of the formed product is about 1.2 to 1.4 times the tap density of the powder and about 2.2 to 2.6 times the loose density of the powder, the production capacity can be significantly increased. However, it also increases the pressure in the furnace when the volatile matter is discharged, causing a dangerous hidden danger of the furnace spraying. Therefore, the present application reserves a through hole of sufficient volume on the formed block product, and after the placement is completed, a sufficiently long airway is formed to lead to the surface of the furnace body, which solves the above-mentioned problem well. Compared with deagglomeration after granulation and then graphitization, the advantage of graphitization after molding is that it significantly increases production capacity, reduces energy consumption, improves the manual working environment, and reduces floor waste during powder transportation. However, from the characteristic parameters of the finished product, the D10 of the particle size volume distribution decreased by 0.3-0.8 μm, which means that the amount of fine powder increased. This is obviously because the crushing after graphitization adds a jaw crusher compared to deagglomeration. If necessary, the increased fine powder can be removed by a classifier, and the product yield decreases by about 1-1.5%.

[0045] Block products such as Figures 1 to 4 As shown, cylindrical, square and other shapes can be used. The molding method is preferably hydraulic molding, and the pressure is preferably 260-360Kg / cm 2 , maintain pressure for 2 to 4 minutes. Within the above range, it can be pressed into a block product with suitable density. The maximum volume density of the block product should not exceed 0.91g / cm 3 Otherwise, excessive fine powder defects and morphological defects will be produced in the subsequent pulverization process.

[0046] In order to improve production efficiency and reduce the defective rate, the maximum diameter / side length of the block product should not exceed 150mm, and the thickness should not exceed 40mm. The through holes are used as exhaust channels. In order to ensure space utilization and product strength, the total area of ​​the through holes should not be greater than 12% of the plane area.

[0047] The maximum diameter or side length of the block product is not greater than 150 mm, more preferably 100 to 150 mm, and the thickness is not greater than 40 mm, more preferably 20 to 40 mm.

[0048] The total area of ​​the through holes is not greater than 12% of the area of ​​the plane where they are located, and the centers of the through holes should be evenly distributed in the length / diagonal / diameter directions. The through holes preferably include a central through hole and a plurality of peripheral through holes distributed around the central through hole, and the diameter of the central through hole is 1.5 to 2 times that of the peripheral through holes, which is conducive to the discharge of the central volatiles, and the diameter of the peripheral through holes is 10 to 13% of the length or diameter of the block product.

[0049] When the block product is cylindrical, when the block products are placed in contact with each other, there is naturally a gap between the cylindrical pressed products, and the gap is filled with resistors to balance the current density at various locations. When the block product is square, a 5-10mm chamfer is set on the edge to prevent defects caused by collisions, which leads to uneven current density in the graphitization furnace. Similarly, when the blocks are placed in contact with each other, resistors are filled in the chamfer gaps to balance the current density at various locations. This application innovates the production process route of artificial graphite secondary particles, reduces the granulation process, and increases the post-graphitization crushing process. The former is a heat treatment equipment with an energy consumption of 100-130 (KW·h) / (day·ton), and the latter is a normal temperature treatment equipment with an energy consumption of 25-35 (KW·h) / (day·ton), which greatly reduces production energy consumption and reduces production costs; and the amount of dust in the pre-carbonization and graphitization processes is greatly reduced, and the working environment of personnel is greatly improved.

[0050] Preferably, in step S1, the particle size of the raw coke is 2 to 15 μm, and the amount of the liquid phase additive is 1 to 15% of the mass of the raw coke. Within the particle size range of the raw coke and the amount of the additive, the raw coke and the liquid phase additive are mixed evenly. The mixing time is preferably 60 to 240 minutes.

[0051] Preferably, the drying temperature in step S2 is 80-150° C., the drying time is 30-150 min, and the drying is performed until the moisture content is ≤1%.

[0052] Preferably, the pre-carbonization temperature in step S3 is 750-900° C. and the time is 240-360 min.

[0053] Preferably, the graphitization temperature in step S4 is 2950-3050° C., and the power supply time is 19-20 hours.

[0054] Preferably, in step S4, the carbonized product is loaded into the graphitization furnace charge chamber for graphitization treatment. Due to the pressing and pre-carbonization, the volume of the block product after graphitization will not shrink further. Figures 5-6 As shown, the method of placing the pressed products in contact with each other is adopted. In order to make the pressed products heated evenly, the resistor material is filled in the material compartment space outside the through hole (i.e., the wall of the carbonized product and the graphitization furnace material compartment), and the resistor material is also filled in the gap between adjacent carbide products to balance the current density everywhere. The particle size of the resistor material is preferably 10 to 15 μm.

[0055] At present, industrial crushers include jaw crushers, ball mills or impact mills, among which industrial jaw crushers can crush to millimeter level, industrial ball mills have a maximum crushing capacity of less than 1 μm, and impact mills have a maximum crushing capacity of less than 3 μm. Generally, the particle size distribution range of finished artificial graphite secondary particles is usually 10 to 25 μm. Therefore, preferably, in step S5, the jaw crusher is first used to crush into millimeter-level particles, and then a ball mill or impact mill is used to continue crushing to the finished product index particle size.

[0056] After crushing by jaw crusher, ball mill or impact mill, in order to ensure that the particle size and purity of the finished product are within the target range, a screening step is also included. After screening, the screened material is separated separately, and the screened material can be demagnetized and packaged.

[0057] In order to improve the yield or adjust the particle size distribution, the crushed material can also be graded.

[0058] Example 1

[0059] S1. The raw coke and coal tar having a particle size in the range of 2 to 15 μm are fully mixed for 120 min, and the amount of coal tar is 8% of the mass of the raw coke;

[0060] S2. Use hydraulic pressure at 300Kg / cm 2 Maintain the pressure for 3 minutes, and press into a square block with a side length of 120 mm and a thickness of 25 mm. The four corners are chamfered with 6 mm, and through holes are reserved on the block. The through holes include a central through hole with a diameter of 21 mm, and four peripheral through holes with a diameter of 14 mm are distributed at a position 42.5 mm away from the center along the diagonal direction; then dry at 110°C for 80 minutes;

[0061] S3. The dried block product is pre-carbonized at 820°C for 300 min to obtain a carbonized product;

[0062] S4. The carbonized product is graphitized at 3000°C for 20 hours to obtain a graphitized product;

[0063] S5. The graphitized product is crushed into millimeter-sized particles by a jaw crusher, and then further crushed by a ball mill, and then sieved to obtain artificial graphite secondary particles with a particle size between 10 and 25 μm.

[0064] Comparative Example 1

[0065] The traditional method is used to produce secondary particles. The specific steps are as follows:

[0066] S1. The raw coke with a particle size in the range of 2 to 15 μm and the high temperature modified asphalt are fully mixed for 90 min, and the asphalt amount is 3% of the mass of the raw coke;

[0067] S2. The mixed material was introduced into a horizontal reactor, heated to 650°C at a heating rate of 5°C / min, and then kept warm for 6 hours. The reactor was cooled to below 50°C to obtain a powder of secondary particles;

[0068] S3. The cooled powder is introduced into a deagglomerator, and the abnormally agglomerated parts are broken up and introduced into a graphitization furnace together;

[0069] S4. After graphitization at 3000°C, a graphitized product of secondary particles is obtained.

[0070] The artificial graphite secondary particles obtained in Example 1 and Comparative Example 1 were analyzed by scanning electron microscope. The results are as follows: Figures 7-8 As shown in Figure 1, through the comparison of electron microscope images, both are obvious secondary particle powders with no significant difference. Table 1 shows the comparison of various indicators, and there is no significant difference either.

[0071] Table 1

[0072]

[0073] Example 2

[0074] S1. The raw coke with a particle size in the range of 2 to 15 μm and the liquid asphalt are fully mixed for 60 min, and the amount of liquid asphalt is 4% of the mass of the raw coke;

[0075] S2. It is hydraulically pressed into cylindrical blocks at 260Kg / cm 2 The molded product was molded under pressure and maintained for 2 minutes. The diameter of the pressed product was 100 mm, the thickness was 20 mm, the diameter of the central through hole was 18 mm, and there were four through holes with a diameter of 12 mm distributed at a distance of 25 mm from the center along the central cross direction. Then, the molded product was dried at 150°C for 30 minutes.

[0076] S3. The dried block product is pre-carbonized at 900°C for 240 min to obtain a carbonized product;

[0077] S4. The carbonized product is graphitized at 3050°C for 19 hours to obtain a graphitized product;

[0078] S5. The graphitized product is crushed into millimeter-sized particles by a jaw crusher, and then further crushed by an impact mill. After screening, artificial graphite secondary particles are obtained, and the particle size is between 10 and 25 μm. The particles are analyzed by scanning electron microscopy. The results are as follows: Fig. 9 The indicators are shown in Table 2.

[0079] Table 2

[0080]

[0081] Example 3

[0082] S1. The raw coke with a particle size in the range of 2 to 15 μm and the asphalt oil are fully mixed for 240 min, and the amount of liquid asphalt is 6% of the mass of the raw coke;

[0083] S2. It is formed into cylindrical blocks by hydraulic pressing. 2 The molded product was formed under pressure and maintained under pressure for 4 minutes. The diameter of the pressed product was 150 mm, the thickness was 40 mm, the diameter of the central through hole was 27 mm, and there were four through holes with a diameter of 18 mm at a distance of 37.5 mm from the center along the central cross direction. Then, the molded product was dried at 80°C for 150 minutes.

[0084] S3. The dried block product is pre-carbonized at 750°C for 360 min to obtain a carbonized product;

[0085] S4. The carbonized product is graphitized at 2950°C for 20 hours to obtain a graphitized product;

[0086] S5. The graphitized product is crushed into millimeter-sized particles by a jaw crusher, and then further crushed by an impact mill. After screening, artificial graphite secondary particles are obtained, and the particle size is between 10 and 25 μm. The particles are analyzed by scanning electron microscopy. The results are as follows: Fig.10 shown.

[0087] Example 4

[0088] S1. The raw coke with a particle size in the range of 2 to 15 μm and the ethanol solution of the phenolic resin are mixed thoroughly for 150 min, the amount of the phenolic resin is 2% of the mass of the raw coke, and the amount of ethanol is enough to just dissolve the resin;

[0089] S2. It is hydraulically pressed into square blocks at 300Kg / cm 2 The molded product was formed under pressure and maintained under pressure for 3 minutes. The side length of the pressed product was 125 mm, the thickness was 30 mm, the four corners were chamfered with 7 mm, the diameter of the central through hole was 22.5 mm, and six through holes with a diameter of 15 mm were evenly distributed on the concentric circle with a diameter of 62.5 mm. Then it was dried at 110 ° C for 70 minutes;

[0090] S3. The dried block product is pre-carbonized at 750°C for 360 min to obtain a carbonized product;

[0091] S4. The carbonized product is graphitized at 3000°C for 19 hours to obtain a graphitized product;

[0092] S5. The graphitized product is crushed into millimeter-sized particles by a jaw crusher, and then further crushed by a ball mill. After screening, artificial graphite secondary particles are obtained, and the particle size is between 10 and 25 μm. The particles are analyzed by scanning electron microscopy. The results are as follows: Fig.11 The indicators are shown in Table 3.

[0093] Table 3

[0094]

[0095] Comparative Example 2

[0096] S1. The raw coke and coal tar having a particle size in the range of 2 to 15 μm are fully mixed for 100 min, with the amount of coal tar being 8% of the mass of the raw coke;

[0097] S2. It is hydraulically pressed into square blocks at 300Kg / cm 2 The molded product was formed under pressure and maintained under pressure for 3 minutes. The side length of the pressed product was 120 mm, the thickness was 25 mm, the four corners were chamfered with 6 mm, and no through holes were set. Then it was dried at 110°C for 80 minutes.

[0098] S3. The dried block product is pre-carbonized at 820°C for 300 min to obtain a carbonized product;

[0099] S4. The carbonized product is graphitized at 3000℃ and the power supply time is 20h. During the graphitization, the furnace spray phenomenon occurs, such as Fig.12 shown.

[0100] Comparative Example 3

[0101] S1. The raw coke with a particle size in the range of 2 to 15 μm and the asphalt oil are fully mixed for 100 min, and the amount of liquid asphalt is 5% of the mass of the raw coke;

[0102] S2.Hydraulic pressing is used to form cylindrical blocks, 290Kg / cm 2 The molded product was formed under pressure and maintained under pressure for 4 minutes. The diameter of the pressed product was 100 mm and the thickness was 30 mm. Four and eight 10 mm through holes were evenly distributed on concentric circles with diameters of 40 mm and 70 mm.

[0103] S3. The dried block product is pre-carbonized at 800°C for 300 min to obtain a carbonized product;

[0104] S4. The carbonized product is graphitized at 3000℃ and the power supply time is 20h to obtain a graphitized product; the graphitized product has a lot of fragmentation, such as Fig.13As shown in the figure, the reason is that there are many through holes with small diameters, and the air passages are blocked when the volatile gas is placed, which causes the volatile gas to gather in a small area when it is discharged and fracturing the molded product. This further causes the local current density in the furnace to be too large or too small, affecting the consistency of the graphitization degree of the product.

[0105] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing artificial graphite secondary particles, characterized in that: The following steps are involved: S1. The raw coke and the liquid additive are fully mixed; the amount of the liquid additive is 1 to 15% of the mass of the raw coke; S2. Pressing and forming into a block product, and reserving through holes on the block product, and then drying; the total area of ​​the through holes is not greater than 12% of the area of ​​the plane where they are located, and the centers of the through holes are evenly distributed in the side length and diagonal, or diameter direction of the block product; the through holes include a central through hole and a plurality of peripheral through holes evenly distributed around the central through hole, and the diameter of the central through hole is 1.5 to 2 times that of the peripheral through holes; the diameter of the peripheral through holes is 10 to 13% of the side length or diameter of the block product; S3. Pre-carbonizing the dried block product to obtain a carbonized product; S4. graphitizing the carbonized product to obtain a graphitized product; during the graphitization, the through holes on the block product form air passages leading to the surface of the graphitization furnace; S5. The graphitized product is crushed to a particle size corresponding to a finished product to obtain artificial graphite secondary particles.

2. The method for preparing artificial graphite secondary particles according to claim 1, wherein The particle size of the raw coke in step S1 is 2-15 μm.

3. The method for preparing artificial graphite secondary particles according to claim 1, wherein The liquid additive in step S1 is one or a combination of two or more selected from coal tar, asphalt oil, liquid asphalt, a toluene-ethanol mixed liquid, and an ethanol solution of a phenolic resin.

4. The method for preparing artificial graphite secondary particles according to claim 1, characterized in that: The molding method in step S2 is hydraulic molding, and the molding pressure is 260~360Kg / cm 2 , maintain pressure for 2~4min.

5. The method for preparing artificial graphite secondary particles according to claim 1, characterized in that, The maximum diameter or side length of the block product is not greater than 150 mm, and the thickness is not greater than 40 mm.

6. The method for preparing artificial graphite secondary particles according to claim 1, characterized in that: The bulk density of the block product is not more than 0.91 g / cm 3 .

7. The method for preparing artificial graphite secondary particles according to claim 1, characterized in that: The drying temperature in step S2 is 80-150°C and the drying time is 30-150 minutes; The pre-carbonization temperature in step S3 is 750-900°C and the time is 240-360 min; The graphitization temperature in step S4 is 2950-3050° C., and the power supply time is 19-20 hours.

8. The method for preparing artificial graphite secondary particles according to claim 1, characterized in that: Step S4: the carbonized products are loaded into a graphitization furnace charge chamber for graphitization treatment. The carbonized products are loaded into the furnace in pairs and placed in contact with each other. Resistor materials are filled in the gaps between the carbonized products and the walls of the graphitization furnace charge chamber, and resistor materials are also filled in the gaps between adjacent carbonized products.

9. The method for preparing artificial graphite secondary particles according to claim 1, characterized in that: In step S5, the pulverization is first performed by jaw crusher to millimeter-sized particles, and then further pulverized by ball mill or impact mill to the target particle size of the finished product, wherein the target particle size of the finished product is 10-25 μm.

Citation Information

Patent Citations

  • Preparation method of low temperature graphite anode material for lithium ion battery

    CN106276910A

  • Lithium battery graphite anode material production process

    CN108101042A

  • Block semi-closed hole catalytic graphitization method for preparing high-capacity synthetic graphite negative electrode material

    CN110416544A

  • Si / CNT / graphite@C composite silicon-carbon negative electrode material as well as preparation and application thereof

    CN112038600A

  • Method for preparing carbon fiber reinforced graphene foam block and related product

    CN114890815A